One dimensional time-domain non-linear site seismic response analysis program integrating two hysteresis models of soil - Yan, Jingru; Zhang, Yushan (Frontiers in Earth Science, 2023)
In the numerical simulation of site seismic responses, traditional equivalent linearization methods typically realized in the frequency domain cannot satisfactorily analyze the high-degree non-linearity of soil under strong input motions. Therefore, the “true” non-linear numerical methods performed in the time domain are often utilized in such cases. However, a crucial element of the time-domain non-linear method, which is the hysteresis model of soil that describes the rule controlling the loading–unloading behavior of soil, has no established guidelines for earthquake engineering. Different researchers presented different models, revealing the epistemic uncertainty related to the dynamic properties of soil. Thus, the time-domain non-linear method should consider this uncertainty in practice. Therefore, in this study, a one-dimensional (1D) time-domain non-linear site seismic response analysis program was developed. The developed program was coded using Fortran95 and integrates two kinds of soil hysteresis models (i.e., extended Masing model and dynamic skeleton curve model). In both models, the damping correction was introduced to calibrate the hysteresis loop area toward the damping ratio measured in the dynamic triaxial test or resonant column test. Moreover, the temporospatial finite difference algorithm was used to resolve the 1D non-linear wave equation, and its precision was demonstrated in comparison with the results of the frequency-domain program for the linear case. Finally, the non-linear seismic response of a specific site was calculated by the proposed program. The findings of the fitting were compared to those of the two popular time-domain non-linear programs DEEPSOIL (Hashash, V6.1) and CHARSOIL (Streeter et al., CHARSOIL, Characteristics Method Applied to Soils, 1974 March 25). Simultaneously, the Japanese KIK-net strong motion observation station data were applied to validate the reliability of this program.